Perancangan Interior Museum Basket Indonesia di Surabaya - Chatarina Regina Soebekti (Intra, 2017)
Basketball is a sport whose development has increased enough at this time in Indonesia. Increasing number of newly formed basketball club, many basketball school, and more people who create new business by building a basketball court, sells equipment, accessories for the needs of basketball. Surabaya is one of the cities that took part in developing basketball in Indonesia, PT. DBL is a company under the auspices of the Jawa Pos Group who took part in developing this sport. The problems that exist at the moment is there is no Indonesian basketball museum at this time, behind the development of basketball at this time, need to record the origin and basketball journey in Indonesia.Therefore it is necessary to be given a container that records it all with the existence of an Indonesian basketball museum. The current problem is the absence of Indonesian basketball museum in Surabaya. So it needs to be solved by creating the design of Indonesian Basketball Museum in Surabaya by using the concept of "D-A-D", with Drills, Attractive, and Dynamic. These three words are derived from words that contain elements of basketball that will be applied to the design of this museum.By applying the concept is expected to meet some goals to be achieved in this design. Provide facilities and facilities that meet the requirements to be a museum that rekreatif, educative and informative for visitors. Provide a place for basketball lovers as well as laity to better understand the sport of basketball, the origin, development and travel of basketball sports and the legendary Indonesian players who have been instrumental in this country. Basketball Museum Indonesia interior creates a comfortable and pleasant through the creation of a new atmosphere of the space and all the nuances of basketball, the whole concept, elements, furniture associated with the basketball hall. So that it can attract visitors and expected future can be one of the attractions of Indonesia in Surabaya.One of the things that can attract visitors to come to this basketball museum is the innovation of the use and application of modern technology, and the use of LED touchscreen display that is almost placed in every corner of the museum room, making this museum into an interactive museum and self service. It also implemented sustainable elements of the interior elements of the material and its former basketball accessories-accessories which are not used anymore and the provision of green plants in every corner of the room on Indonesia's Basketball Museum.